GANRANG PAâBALLE DALAM RITUAL ACCERAâ KALOMPOANG DI KALANGAN BANGSAWAN GOWA - SULAWESI SELATAN - Razak, Amir (Institut Seni Indonesia Padang Panjang, 2011)
Ganrang Paâballe is an ensemble consisting of two pairs of ganrang (drum), a piuk-puik (flute), and a dengkang (gong). This ensemble is usually performed in traditional or ritual ceremonies among Makassar ethnic group. Among the aristocrat group, this music is routinely performed each year in the ritual ceremony to clean Gowa kingdomâs royal objects, which is usually called upacara acceraâ kalompoang. The presentation of Ganrang Paâballe has structured patterns of rhythm. The patterns are Tunrung balle sumangeâ (to boost the spirit or soul), tunrung rua (two-rhythm stroke), and tunrung pakanjara (pakanjara stroke). The three patterns must be played with a structure in a kalompoang ritual ceremony. Apart from a ritual ensemble, Ganrang Paâballe is also considered as a heritage of Gowa kingdom (kalompoang). Non-existence of this music in a ritual ceremony is believed to be a problem in kalompoang. Without the sound of the drum, the ceremony will lose its spirit. In addition to that, it will dishonor the spirit of the late aristocrats which is believed to be residing in every royal objects. Â